Epigenetic inactivation of LHX6 mediated microcystin-LR induced hepatocarcinogenesis via the Wnt/β-catenin and P53 signaling pathways. (September 2019) - Chen, Hong-qiang; Zhao, Ji; Li, Yan; Huang, Yu-jing; Chen, Dong-jiao; He, Li-xiong; Wang, Ling-qiao; Zheng, Chuan-fen; Wang, Jia; Cao, Jia; Shu, Wei-qun; Liu, Jin-yi; et al.
Abstract: Microcystins (MCs) have been shown to be carcinogenic by animal and cellular experiments and found to be associated with the development of human hepatocellular carcinoma (HCC) through epidemiological studies. However, the molecular mechanism of microcystin-LR (MC-LR) induced HCC is still unclear. This study is determined to clarify the role and mechanism of LHX6 in MC-LR-induced hepatocarcinogenesis. Using the previously established MC-LR-induced malignant transformation model in L02 cells, we screened out LHX6, homeobox gene that was significantly changed. We found that LHX6 was significantly down-regulated in MC-LR treated L02 cells and the liver tissue of rats treated for 35 weeks with 10 μg/kg body weight of MC-LR. Expression of LHX6 in human tumor tissue was significantly down-regulated in high MC-LR-exposure group. LHX6 was hypermethylated in MC-LR treated L02 cells and up-regulated after treatment with 10 μM of 5-aza-2′-deoxycytidine. Furthermore, overexpression of LHX6 inhibited proliferation, invasion and migration of malignantly transformed L02 cells in vitro and in vivo, while knockdown of LHX6 resulted in an opposite phenotype. In addition, we found that up-regulation of P53 and Bax resulted in apoptosis, and that down-regulation of CTNNB1 and MMP7 led to migration of MC-LR treated L02 cells. Blockade of P53 and CTNNB1 by its inhibitor significantly diminished the effect of LHX6. These genes were working together during the process of MC-LR-induced hepatocarcinogenesis. Our study demonstrated for the first time that LHX6 gene expression is regulated by DNA methylation and can inhibit the proliferation, invasion and migration through Wnt/β-catenin and P53 signaling pathways during the MC-LR-induced hepatocarcinogenesis. This result may suggest that LHX6 gene can be used as a potential target gene and a biomarker for liver cancer treatment. Graphical abstract: Image 1 Highlights: LHX6 was significantly down-regulated in MC-LR induced hepatocarcinogenesis. DNA methylation regulated LHX6 gene expression during MC-LR induced hepatocarcinogenesis. LHX6 inhibited proliferation, migration and invasion of MC-LR induced malignantly transformed L02 cells in vitro and in vivo. LHX6 plays a tumor suppressing role in MC-LR-induced liver cancer through the Wnt/β-catenin and P53 pathways.